Effects of even and odd number fatty acids cofeeding on PHA production and composition inPseudomonas putidaBet001 isolated from palm oil mill effluent - Mohd Razaif-Mazinah, M.R.; Annuar, M.S.M.; Sharifuddin, Y. (Wiley, 2015)
The biosynthesis of medium-chain-length poly-3-hydroxyalkanoates by Pseudomonas putida Bet001 cultivated on mixed carbon sources was investigated. The mixed carbon sources consisted of heptanoic acid (HA) and oleic acid (OA). A relatively low PHA content at 1.2% (w/w) and 11.4% (w/w) was obtained when HA or OA was used as the sole carbon source. When these fatty acids were supplied as a mixture, PHA content increased threefold. Interestingly, the mixture-derived PHA composed of both odd and even monomer units, namely. 3-hydroxyheptanoate, 3-hydroxyoctanoate, 3-hydroxydecanoate, and 3-hydroxydodecanoate and no unsaturated monomer was detected. It is hypothesized that the even-numbered monomers were derived primarily from OA, whereas the odd-numbered monomer was derived from HA. This also points out to an efficient and yet distinct fatty acids metabolism that fed the PHA biosynthesis machinery of this particular microorganism. PHA obtained was elastomeric because melting temperature (Tm) and crystallinity were absent. It showed good thermal stability with degradation temperature (Td) ranging from 275.96 to 283.05 °C.